Long-term autobiographical memory across middle childhood: patterns, predictors, and implications for conceptualizations of childhood amnesia. Issue 9 (21st October 2019) - Bauer, Patricia J.; Larkina, Marina; Güler, Evren; Burch, Melissa
ABSTRACT: We examined recall of events by children 4–11 years to inform patterns of retention of autobiographical memories as well as factors that predict their survival. 101 children participated in a 4-year prospective study. At study inception, children were 4, 6, and 8 years. They were tested annually for three more years for a total of four waves of data collection. At each wave, we obtained narrative reports of recent (all waves) and distant (Waves 2–4) events, resulting in virtually continuous sampling of memories formed by 4- to 11-year-olds and recalled after 1–3-year delays. We also measured children's language, and domain-general and memory-specific cognitive skills. Multi-level modelling revealed age-related increases in the likelihood of survival of memories over the delays. Critically, the rate of increase in retention of individual memories was the same across the cohorts. In addition to age, thematic coherence of original memory reports predicted memory survivability. Other factors were not predictive. The dense sampling and prospective tracking of memories across the 4–11-year age period permitted an especially strong test for continuity versus discontinuity in autobiographical memory across the second half of the first decade of life. The data are strongly indicative of continuity and gradual change.